ANALISIS PENJUALAN DAN LABA SEBELUM DAN SESUDAH IMPLEMENTASI QRIS PADA WARUNG BAKMI TKTDW PERIODE JULI 2021 SAMPAI JUNI 2023 - Setyowati, Hasanah; Halimah, Ajeng ‘Aini; Kundala, Manendha Maganitri (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This study aims to analysis sales and profit before and after implementation of QRIS in food stall of Bakmi Jawa TKTDW. QRIS is a QR Code standard created by Bank Indonesia to facilitate digital payments through server-based electronic money applications, electronic wallets and mobile banking. Standardization is carried out so that transactions using QR Codes are easier, faster and safer. The method used in this research is qualitative method, descriptive analysis techniques. Data is collected by doing interviews and using secondary data. The secondary data collected is income statement from Bakmi TKTDW. The results of this research show that: (1) before implementation of QRIS do not affect sales and profit and (2) after implementation of QRIS do not affect sales and profits.